Modifikasi Pati Secara Asetilasi dan Aplikasinya Sebagai Bahan Dasar Filamen Jaring Ikan Ramah Lingkungan - Triastuti, Warlinda Eka; Suprapto, Suprapto; Muyassaroh, Tisnuliah; Bawafi, Suardhana; Sampurno, Ade Citra Oktaviana Elok; Meghotsah, Muhammad Akha; Aditama, Fitra Diannico; Ardhana, Krisna Setya (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2023)
Fishing nets are generally made of synthetic polyamides such as nylon. The use of nylon nets has negative impacts, such as habitat destruction. So it is necessary to consider the use of biodegradable nets. One of the potential natural materials that can be used as eco-friendly fishing net filaments is starch. The research aims to modify cassava and corn starch by acetylation method to improve their characteristics. Starch modification was carried out by adding acetic acid with variable concentrations of 10%, 15%, 20%, 25%, and 30% into the starch. Modified starch was analysis for water content, swelling power, solubility, and FTIR. In the manufacture of filaments using modified corn 15% with a test result of 0.04; 0.13; 0.05. The results of the FTIR analysis showed a combined functional group between HDPE and starch at wave numbers 2922.2cm-1 and 1371.7cm-1. Starch content has an effect on reducing the weight of filament degradation. SEM analysis showed that the compatibility of the filament with the addition of MA increased but the internal structure of the filament gradually expanded with increasing starch content. The results of the analysis of tensile strength and elongation at break of the filament are 1.81 kgf and 119.77%